Epidemiologia da hanseníase na 11° região de saúde do Pará: análise do período de 2010 a 2020 - COSTA, Leandro Araújo (2023)
Objectives: To trace the epidemiological profile of the leprosy in the 11th Health Region of Pará, from 2010 to 2020. Method: This is a cross-sectional, descriptive, retrospective epidemiological study with a quantitative approach, based on secondary data collections, reported in the System of Notifiable Diseases Information (SINAN), from 2010 to 2021. Data were organized in Excel spreadsheets and statistically analyzed in Bioestat 5.3. Results: During the period from 2010 to 2020, 9,863 cases of leprosy were reported in the 11th Health Region of Pará, with 7,966 new cases, with an average of 896 notifications/year. Despite the large decline in the annual detection rate of leprosy in the region, based on the first and last year of the survey (2010-2020), the region is still in the Very High Endemicity profile, with 29 cases per 100,000 inhabitants/year. The profile of leprosy cases in the region is predominantly male (62.4%), between 15 and 50 years old (60.6%), brown (67.8%) and with a low level of education (73.9%). Mostly Multibacillary (68%) and Dimorphic (57%), reflecting high percentages of disabilities (27%) and new cases in children under 15 years of age (12.6%). Approximately, 792 cases went undiagnosed, adding a 29.9% increase in prevalence, resulting in a real prevalence of 3438 cases (29/10,000 population) in the period. In other words, it can be said that 23% of the cases were not diagnosed and, consequently, went untreated, maintaining the active cycle of leprosy in the region. This is a characteristic of regions classified as hyperendemic. Conclusion: It is concluded that leprosy is a public health problem in the region, with high rates of disability, under 15 years and hidden cases, requiring interventions in various spectrums, such as active casework, better monitoring of treatment, training of professionals about the disease and its attributions, as well as health education for the population on the subject.